2019
DOI: 10.1002/dev.21833
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol in the perinatal period mediates associations between maternal adversity and disrupted maternal interaction in early infancy

Abstract: Existing literature points to the possibility that cortisol could be one link between maternal adversity and poorer parenting quality, but most studies have examined salivary cortisol concentrations rather than hair cortisol concentrations. The current study examined hair cortisol concentration (HCC) during the third trimester of pregnancy as a mediator between maternal adversity indicators (childhood abuse, severe mental illness, symptomatic functioning) and maternal caregiving behavior at 4 months postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
1
24
0
1
Order By: Relevance
“…This finding adds to the literature on the continuity of depressive symptoms over the first year and for several years postpartum (e.g., Alpern & Lyons‐Ruth, ; Edwards & Hans, ; Lyons‐Ruth, Zoll, Connell, & Grunebaum, ) and indicates that mothers likely to experience postpartum depressive symptoms may already be showing elevated symptoms during pregnancy. Similarly, other work provides evidence of strong continuity in more general symptomatic functioning from the third trimester of pregnancy to 4‐month postpartum (Nyström‐Hansen et al, ). This continuity in symptomatic functioning from pre‐ to postpartum periods supports the identification of at‐risk women in pregnancy, as well as the implementation of preventive interventions prior to the birth of the child to minimize disruption in the mother's early interactions with her infant.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This finding adds to the literature on the continuity of depressive symptoms over the first year and for several years postpartum (e.g., Alpern & Lyons‐Ruth, ; Edwards & Hans, ; Lyons‐Ruth, Zoll, Connell, & Grunebaum, ) and indicates that mothers likely to experience postpartum depressive symptoms may already be showing elevated symptoms during pregnancy. Similarly, other work provides evidence of strong continuity in more general symptomatic functioning from the third trimester of pregnancy to 4‐month postpartum (Nyström‐Hansen et al, ). This continuity in symptomatic functioning from pre‐ to postpartum periods supports the identification of at‐risk women in pregnancy, as well as the implementation of preventive interventions prior to the birth of the child to minimize disruption in the mother's early interactions with her infant.…”
Section: Discussionmentioning
confidence: 78%
“…The current results cannot speak to the potential continuity in HCC from pregnancy to the postpartum period. However, Nyström‐Hansen et al () found robust continuity in HCC levels from the third trimester of pregnancy to infant age 4 months, and hair cortisol levels at both time points were associated with maternal disrupted interaction in the SFP. Thus, the effects of elevated HCC during pregnancy obtained here may possibly be linked to the continuation of elevated HCC into the postpartum period.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, two studies found that elevated maternal HCC during pregnancy mediated disrupted mother-child interaction in early infancy. 26,41 These results suggest that maternal stress (i.e. psychiatric symptoms) is inconsistently related to maternal and/or infant HCC, but independently, maternal HCC seems to influence infant cortisol and mother-child interaction both in the early postpartum period and beyond.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 88%
“…This evidence leads to the hypothesis that chronic overactivation of the stress response leads to blunted HPA axis activity over time, indicating that the severity and duration of stress activity might be a more important determinant of basal cortisol levels in patients with severe and long-lasting psychiatric disorders than the nature of the psychiatric diagnosis. 25,26 Maternal HPA axis functioning and its influence on the foetus Altered HPA axis activity in mothers who suffer from severe psychiatric disorders can influence the foetus through intrauterine programming of the HPA axis. 19,27 There is some evidence that these early alterations in HPA axis functioning contribute to vulnerability to psychiatric disease in offspring later in life, 28 by early fine-tuning of the HPA axis set point.…”
Section: Hpa Axis and Psychiatric Disordersmentioning
confidence: 99%